A new screening method for identifying chemosensory receptors responding to agonist. Issue 6 (9th March 2021) - Tsuchiya, Sakura; Terada, Yuko; Matsuyama, Minami; Yamazaki-Ito, Toyomi; Ito, Keisuke
ABSTRACT: Humans sense taste and smell of various chemical substances through approximately 430 chemosensory receptors. The overall picture of ligand–chemosensory receptor interactions has been partially clarified because of numerous interactions. This study presents a new method that enables a rapid and simple screening of chemosensory receptors. It would be useful for identifying chemosensory receptors activated by taste and odor substances.